Messaging and Mask Wearing: How Political Identity Affects Pro-Mask Message Effectiveness - Vinick, Ty A. (Tufts Archival Research Center, 2021)
This paper seeks to answer the question: Is responsiveness to Pro-Mask Messaging impacted by the political affiliations of the sender and receiver of the message? As mask-wearing behaviors have become a primary form of defense against the coronavirus pandemic, maximizing mask wearing within the population has become vital. Understanding how individuals of different political affiliations respond to pro-mask messaging from politicians, both from within and outside of their party, could prove beneficial in maximizing individual mask wearing response.